A Series Of Comprehensive Optimization Models For Surface Mine Long-Term Planning - Zhang Youdi (Society for Mining, Metallurgy & Exploration, 1989)
According to general guidelines, deposits suitable for surface mining can be divided into two basic categories: horizontal or flat-bedded deposits and inclined or dip-buried deposits. A series of mathematical models for surface mine long-term planning (SMLTP) has been developed and can be used for any kind of deposit. The basic theory and methodology of the models are oriented- graph simulation which combines graph and network theory with a systems simulation technique to form a new approach. From the viewpoint of surface mining and long-term plan modeling, the main differences between the two categories of deposits are analyzed, an important algorithm is put forward, and the structure of the models and some results of applications are introduced. Dynamic and comprehensive optimizations have been completed by the SMLTP model series. Combining different OR branches, the new approach has been proved to be a powerful tool to solve the strategic problems of surface mine planning.